2009
DOI: 10.1103/physrevlett.103.016401
|View full text |Cite
|
Sign up to set email alerts
|

Turning a Nickelate Fermi Surface into a Cupratelike One through Heterostructuring

Abstract: Using the local density approximation and its combination with dynamical mean-field theory, we show that electronic correlations induce a single-sheet, cuprate-like Fermi surface for hole-doped 1/1 LaNiO3/LaAlO3 heterostructures, even though both eg orbitals contribute to it. The Ni 3d 3z 2 −1 orbital plays the role of the axial Cu 4s-like orbital in the cuprates. These two results indicate that "orbital engineering" by means of heterostructuring should be possible. As we also find strong antiferromagnetic cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
291
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(312 citation statements)
references
References 20 publications
18
291
3
Order By: Relevance
“…From the single-site DMFT calculations with a double-counting energy as another tuning parameter, Wang et al 21 showed that there is a well defined N c , that is, the critical value of d-valency of transition metal; the system is metallic if Relative orbital occupation in the two e g orbitals is a central quantity in understanding LNO/LAO systems 9,12,14,15 . The orbital polarization can be nonzero due to the translation symmetry breaking induced by heterostructuring while the bulk polarization is 0.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the single-site DMFT calculations with a double-counting energy as another tuning parameter, Wang et al 21 showed that there is a well defined N c , that is, the critical value of d-valency of transition metal; the system is metallic if Relative orbital occupation in the two e g orbitals is a central quantity in understanding LNO/LAO systems 9,12,14,15 . The orbital polarization can be nonzero due to the translation symmetry breaking induced by heterostructuring while the bulk polarization is 0.…”
Section: Resultsmentioning
confidence: 99%
“…Since previous calculations were performed at the LDA 14 or DMFT level 12,15 and assumed the bulk-like PM phase, LDA+U calculation can provide meaningful information especially regarding the magnetism in this system. Our total energy calculations showed that the Ni spins order ferromagnetically within the LNO layer, and the inter-layer couplings are also ferromagnetic (FM).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Already the first DFT+DMFT calculations allowed for a better understanding of the Mott-Hubbard transition in V 2 O 3 , 22) of δ-Pu, 23) the Ce volume collapse, 22) and magnetism in Fe and Ni. 24) More recently, among others, iron pnictides and their fluctuating magnetic moment, [25][26][27] complex oxide heterostructures, [28][29][30][31][32] nanoscopic structures, 33,34) thermoelectricity, [35][36][37] spin-orbit interactions, 38,39) and electronic entanglement 40) have been addressed.…”
Section: Introductionmentioning
confidence: 99%